Teacher’s Perceptions Approaches, and Roles to Foster Learners’ Autonomous Learning - Dian Muhammad Rifai; Sukma Shinta Yunianti (International Journal of Seocology, 2021)
An autonomous learning emphasizes learners’ responsibility in their own learning process. Nonetheless, it does not mean that learners’ learn by themselves without teacher’s guidance. Thus, teachers must understand the concept of autonomous learning, their own competence, and their approaches to develop learners’ autonomous learner. The objectives of this study are to identify the teacher’s perception about autonomous learning and the teacher’s approaches to develop autonomous learning for the learners. The participants of this study are an English lecturer and students at the second semester of 2017/2018 academic year. A case study is applied in this qualitative research. The qualitative data are obtained from interview and observation.The findings show that (1) the teacher agrees that autonomous learning will give positive impact to the learners’ learning process as long as they consistent to read up, realize that learning is for their need and can collaborate with the teacher during teaching learning process. It is because autonomous learning is not the only one factor that influences the learners’ intelligence. It is one of learners’ ways in their learning process. Hence, the teacher is still needed to help learners in learning process. (2) The teacher mostly uses teacher-based approach and learner-based approach as his approach to develop the learners’ autonomous learning. It happens because between the teacher and the learners are interdependent each other. Furthermore, the teacher needs to be more closed to the learners so he can motivate themintrinsically. (3) The teacher realizes that he must teach, educate, and motivate the students. It is line with the concept of 2013 curriculum, i.e. the shift of teacher-centeredness to students-centeredness. The main teacher’s responsibility is in supporting students become actively involved in teaching learning process. Thus, in developing students’ autonomous learning, the teacher cannot only function as the source of knowledge for his students anymore.